2010
DOI: 10.1111/j.1748-7692.2010.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Craniometric variation of some Mediterranean and Atlantic populations of Stenella coeruleoalba (Mammalia, Delphinidae): A three‐dimensional geometric morphometric analysis

Abstract: The variability of cranial features of Atlantic and Mediterranean samples of Stenella coeruleoalba was examined using a three‐dimensional geometric morphometric approach. Data were collected on 79 skulls from the upper and middle Mediterranean Sea, the Atlantic French coasts, and Scotland. Three‐dimensional x, y, and z coordinates of 27 landmarks were recorded on each left half skull using a Microscribe 3‐D digitizer. All configurations were rotated, centered, and scaled, and residuals from the mean configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…Although the longer rostrum suggests a decreasing of the mechanical advantages at the tip (Preuschoft and Witzel, ; Segura and Prevosti, ; Segura et al, ), its length, associated with a well‐developed temporal musculature, also implies a gain in mouth‐closing speed at the tip, making prey catch function in adults more efficient. These observations are in agreement with those by Loy et al (), who suggested that the elongation of the rostrum might be related to differences in feeding habits for different populations on Stenella coeruleoalba .…”
Section: Discussionsupporting
confidence: 93%
“…Although the longer rostrum suggests a decreasing of the mechanical advantages at the tip (Preuschoft and Witzel, ; Segura and Prevosti, ; Segura et al, ), its length, associated with a well‐developed temporal musculature, also implies a gain in mouth‐closing speed at the tip, making prey catch function in adults more efficient. These observations are in agreement with those by Loy et al (), who suggested that the elongation of the rostrum might be related to differences in feeding habits for different populations on Stenella coeruleoalba .…”
Section: Discussionsupporting
confidence: 93%
“…Some morphological aspect described here and by those authors, namely the downward inflexion of the rostrum and the ventral displacement of the foramen magnum seems to be common not only to ontogenetic trends, but also for between (Galatius 2010) and within species variation (Loy et al 2010). While these aspects are suggested to be related to foraging in shallow waters (Monteiro-Filho et al 2002), forms with the rostrum more aligned with the vertebral column, such as the ones associated with older individuals here, are though to be related do pelagic feeding (Galatius 2010;Loy et al 2010). The reoccurrence of these morphological patterns within Delphinidae, its correlation with ontogenetic trends and its apparent correlation with different aquatic habitats, suggests that there might be an underling genetic and developmental phenomenon that could facilitate adaptation to different environments (Schluter 1996).…”
Section: Monteiromentioning
confidence: 79%
“…In comparison to surface-based methods, a point MicroScribe digitizer is a quick and cheap method to collect small to intermediate sets of landmarks (Vu et al, 2017). It has been used in various fields, including anthropology and primatology (e.g., Aung et al, 1995;Cardini & Elton, 2008;Mehta & Marinescu, 2001;Mitteroecker et al, 2004;O'Higgins & Jones, 1998;Ross & Williams, 2008;Sholts et al, 2011;Singleton, 2002;Vidarsdottir et al, 2002;Von Cramon-Taubadel et al, 2007), medicine (e.g., Chen et al, 2008;Dastane et al, 1996), and zoology (e.g., Loy et al, 2011;Milne et al, 2009;Owen et al, 2014).…”
Section: Microscribe Digitizermentioning
confidence: 99%